Wrapping an organic reducing reagent in a cationic boron complex and its use in the synthesis of polyhalide monoanionic networks - Vitske, Viktoriia; Herrmann, Hendrik Hans; Enders, Markus; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2012)
The reaction between BF3⋅OEt2 and one of two guanidines, 1,8-bis(tetramethylguanidinyl)naphthalene (btmgn) and 1,2,4,5-tetrakis(tetramethylguanidinyl)naphthalene (ttmgn), yields the salts [(btmgn)(BF2)]BF4 and [(ttmgn)(BF2)2](BF4)2. NMR spectroscopic data show that the boron atoms in the cation and anion exchange in the case of [(ttmgn)(BF2)2](BF4)2, but not in the case of [(btmgn)(BF2)]BF4. The rate constant for this exchange was estimated to be 4 s−1 at 80 °C for solutions in CH3CN. These salts were subsequently used for the reduction of dihalides Br2 or I2 to give polyhalide salts. We report the synthesis and first complete characterization (including structural analysis) of salts that contain pentabromide monoanions. In these salts, the Br5− anions interact to give dimeric units or polymeric chains. Our results are compared to previous quantum chemical calculations on the gas-phase structure of the Br5− anion. The possible pathways that lead to the polyhalides are evaluated. In the case of [(ttmgn)(BF2)2](BF4)2, reduction is accompanied by ttmgn oxidation, whereas in the case of [(btmgn)(BF2)]BF4 reduction is initiated by aromatic substitution.
Gesehen am 10.10.2018